Analisa Potensi Gelombang Laut sebagai Sumber Energi Terbarukan Menggunakan Perangkat Oscillating Water Column (OWC) Di Wilayah Perairan Laut Timor - Jasron, Jahirwan Ut; Mangesa, Daud P.; Boimau, Kristomus; Tarigan, Ben V.; Maliwemu, Erich U.K.; Salombe, Mexin (Universitas Nusa Cendana, 2022)
An in-depth study is needed on the use of alternative energy to overcome human energy needs. This study aims to analyze the potential of ocean wave energy that can be converted by the